Social inclusion of disable people: achievements, challenges and implications for the nursing area - França, Inacia Sátiro Xavier de; Pagliuca, Lorita Marlena Freitag (Revista da Escola de Enfermagem da USP, 2009)
This study aimed to understand the testimonies of disabled people about the concreteness of the social inclusion process, as well as to articulate their testimonies with the directives of Law 3289/99. Eighteen people were interviewed, six of which were physically disabled, six visually disabled, and six had hearing disabilities. Data were standardized and categorized in two meaning cores: pre-inclusivist and inclusivist guidelines of the disabled person. The methodological perspective was discourse analysis. In conclusion, these subjects had achievements in legislation that guarantees their rights to citizenship, but there are challenges in the areas of healthcare, education, professional training and insertion in the job market. The rehabilitation nurses must know the experiences of these subjects and their relatives to help them with strategies of coping for the problems affecting their inclusion, and consequently their health.